Intestinal Microbiota Disruption Reduces Regulatory T Cells and Increases Respiratory Viral Infection Mortality Through Increased IFNγ Production - Grayson, Mitchell H.; Camarda, Lauren E.; Hussain, Syed-Rehan A.; Zemple, Sarah J.; Hayward, Michael; Lam, Vy; Hunter, Desiré A.; Santoro, Jennifer L.; Rohlfing, Michelle; Cheung, Dorothy S.; Salzman, Nita H. (Frontiers in Immunology, 2018)
Alterations in gastrointestinal microbiota indirectly modulate the risk of atopic disease, but effects on respiratory viral infections are less clear. Using the murine paramyxoviral virus type 1, Sendai virus, we examined the effect of altering gastrointestinal microbiota on the pulmonary antiviral immune response. C57BL6 mice were treated with streptomycin before or during infection with Sendai virus and resulting immune response studied. Ingestion of the non-absorbable antibiotic streptomycin led to a marked reduction in intestinal microbial diversity without a significant effect on lung microbiota. Reduction in diversity in the gastrointestinal tract was followed by greatly increased mortality to respiratory viral infection (p < 0.0001). This increase in mortality was associated with a dysregulated immune response characterized by decreased lung (p = 0.01) and intestinal (p = 0.03) Treg cells, and increased lung IFNγ (p = 0.049), IL-6 (p= 0.015), and CCL2 (p = 0.037). Adoptive transfer of Treg cells or neutralization of IFNγ prevented increased mortality. Further, Lin–CD4+ cells appeared to be a potential source of the increased IFNγ. Together these results demonstrate gastrointestinal microbiota modulate immune responses at distant mucosal sites, and have the ability to significantly impact mortality in response to a respiratory viral infection.